Expert System of Heart Attack Prediction - Kayalvily, Tabianan; Chew, Lian Wei; Deshinta, Arrova Dewi (INTI International University, 2019)
Nowadays, heart attack become most common deadly disease in modern era. More than 80% of heart attack deaths happening in low-income and middle-income countries. The reason why these two income countries have the highest rates of heart attack deaths that is due to their financial constraints. This led some of them die of heart attack because they did not know their condition in advance. In order to prevent heart attack death rate increasing, the author develop an expert system that allow users to check their heart status with their mobile phone. By using this system, they can early know about their heart status and can early know if they are having a heart attack risk. For develop this proposed system, the author will be using Android technology to develop the proposed system. Next, the author also will be uses decision table to analyze the result. The research methodology will be use in this proposed project is prototyping.